PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA MODIFIKASI RANGKA KENDARAAN BERMOTOR RODA DUA DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA DUMAI - Simon Albertian Redy S; Mexsasai Indra; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
According to Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation Article 277 "Any person who enters a motor vehicle, trailer, and attached train into the territory of the Republic of Indonesia, manufactures, assembles, or modifies which causes a change in type, train. trailer, attached carriage, and special vehicles operated domestically that do not fulfill the type test obligation, will be subject to a maximum imprisonment of 1 year or a maximum fine of Rp. 24,000,000 ", but in practice there are still many motorists who modify motorized vehicles without paying attention to the provisions. - the provisions in the Law. This research is a sociological legal research, which is a study that seeks to see the unity between law and society with the gap between das sollen and das sein. The nature of this research is descriptive research, which is a method intended for exploration and clarification of a social phenomenon or reality by describing a number of variables relating to the problem and the unit under study. The data source is secondary data which is divided into 3 (three), namely primary, secondary and tertiary legal materials. The purpose of this study was to determine how law enforcement, constraints, and how the efforts to apply to traffic violations related to law enforcement against traffic violations in the form of violations of two-wheeled motor vehicle modification in the legal area of the Dumai City Police. From the results of the research, firstly about how law enforcement against perpetrators of violations of two-wheeled motor vehicle modification in the jurisdiction of the Dumai City Police, secondly What are the obstacles to law enforcement against traffic violations in the form of violations of two-wheeled motor vehicle modification crimes in the jurisdiction of the Resort Police. Dumai City, and third. How are the law enforcement efforts against traffic violations in the form of violations of the criminal act of modification of two-wheeled motor vehicles in the jurisdiction of the Dumai City Police.Keywords: Law Enforcement, Traffic Crime, Traffic Offenses, Modifications, Motor